IMPORTANCE OF FIRE SAFETY AND MAJOR RISK FACTORS IN COTTON PROCESSING ENTERPRISES - Fayzullayev Dedaxuja Zokirjon o’g’li (Web of Journals Publishing, 2024)
Cotton processing enterprises require a specific approach and systematic measures to reduce fire risk. This article examines the importance of fire safety in cotton processing, the main risk factors, and methods to mitigate these risks. The study analyzes the effectiveness of telemetry systems and safety measures in enhancing fire safety.
Keywords: Cotton processing, fire safety, telemetry systems, dust, sensors, technological equipment, fire risk, enterprise safety, integrated systems, warning systems.